Outpatient Management of Patients With Angina With No Obstructive Coronary Arteries: How to Come to a Proper Diagnosis and Therapy - Meeder, Joan G.; Hartzema-Meijer, Mariëlle J.; Jansen, Tijn P. J.; Konst, Regina E.; Damman, Peter; Elias-Smale, Suzette E. (Frontiers in Cardiovascular Medicine, 2021)
Two-thirds of women and one-third of men who undergo a clinically indicated coronary angiography for stable angina, have no obstructive coronary artery disease (CAD). Coronary vascular dysfunction is a highly prevalent underlying cause of angina in these so called “Angina with No Obstructive Coronary Arteries (ANOCA)” patients, foremost in middle aged women. Coronary vascular dysfunction encompasses various endotypes, namely epicardial and microvascular coronary spasms, impaired vasodilatation, and increased microvascular resistance. ANOCA patients, especially those with underlying coronary vascular dysfunction, have an adverse cardiovascular prognosis, poor physical functioning, and a reduced quality of life. Since standard ischemia detection tests and coronary angiograms are not designed to diagnose coronary vascular dysfunction, this ischemic heart disease is often overlooked and hence undertreated. But adequate diagnosis is vital, so that treatment can be started to reduce symptoms, reduce healthcare costs and improve quality of life and cardiovascular prognosis. The purpose of this review is to give a contemporary overview of ANOCA with focus on coronary vascular dysfunction. We will provide a possible work-up of patients suspected of coronary vascular dysfunction in the outpatient clinical setting, based on the latest scientific insights and international consensus documents. We will discuss the value of ischemia detection testing, and non-invasive and invasive methods to diagnose coronary vascular dysfunction. Furthermore, we will go into pharmacological and non-pharmacological therapeutic options including anti-anginal regimens and lifestyle interventions.